Pobreza, raça e gênero: famílias de detentas em João Pessoa/PB - Santos, Anna Paula Batista dos (2020)
The social processes that constituted our country were marked by violence and elimination of individuals such as dangerous. Among these people, black, poor and peripheral women present themselves as one of the target audiences of eugenic discourses and practices. These women, who are often primarily responsible for supporting their families, suffer prejudice and discrimination from society, and if they have a family member imprisoned, this stigma increases. Thus, the main objective of this paper was to analyze the reality of detainees' families based on poverty, race and gender.For this purpose, I examined the construction of a nation's ideal for Brazil in the late nineteenth century that aimed at a true massacre of the population that lived here. I also discussed the trajectory of life and reality of black women, symbols of strength and resistance, who suffer various violations of rights and are discriminated mainly if they have any imprisoned relatives. Finally, I brought the analysis and discussion of the data collected through semi-structured interviews and interpreted from the discourse analysis. This research was classified as qualitative, literature review, documentary and field. The results indicated that the detainees' relatives are mostly women, black, from the periphery who suffer numerous rights violations and who struggle to survive and still ensure the support of their incarcerated family member. These people are stigmatized by society, are part of the so-called “dangerous classes” and are the objects of normalizing and standardizing discourses and practices.